THE DAWN OF HUMAN REJUVENATION: FROM SCIENCE FICTION TO CLINICAL REALITY : A COMPREHENSIVE REVIEW OF CELLULAR REPROGRAMMING, SENOLYTICS, AND EPIGENETIC INTERVENTIONS (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
Human aging, once considered an immutable biological certainty, is now being actively targeted by scientific interventions that demonstrate measurable age reversal at the cellular and organismal levels. This comprehensive review examines three primary therapeutic modalities leading the rejuvenation revolution: partial cellular reprogramming using Yamanaka factors, senolytic therapies targeting senescent cells, and epigenetic reprogramming through methylation-supportive interventions. Drawing from recent clinical trials, preclinical studies, and market analysis, we present evidence that biological age reversal of 4-11 years has been achieved in human subjects through non-pharmacological interventions, while cellular reprogramming has extended median remaining lifespan by 109% in aged murine models. The longevity biotechnology sector has attracted over $7.5 billion in investment between 2022-2025, signaling unprecedented institutional confidence in aging as a tractable therapeutic target. This article synthesizes current evidence for rejuvenation biology, addresses safety considerations and translational challenges, and projects the trajectory toward human clinical applications.